A new value-weighted total return index for the Finnish stock market - Peter Nyberg; Mika Vaihekoski (Bank of Finland, 2009)
This paper presents a new monthly value-weighted, all-share total return index for the Finnish stock market. The index covers the period from the establishment of the Helsinki Stock Exchange in October 1912 to the beginning of 1970, after which the WI index by Berglund et al (1983) and later in December 1990, the Exchange s own HEX index are available. When combined, these can be used to study the development of the Finnish equity market without a break from the beginning of the stock market until the present day. We also provide a detailed description of the construction methodology and a comparison between our index and those available earlier. The new index replaces the Unitas price index, which has been the only index available for long-term studies from 1928 onwards. The new index also provides an alternative to the book equity weighted Poutvaara (1996) price index for the period 1912 1929.
URN:NBN:fi:bof-20140807491
Keywords: 330